BALANCED DIET IN CHILDHOOD — THE FOUNDATION OF A HEALTHY LIFE - T.E. Borovik; N.N. Semenova; T.N. Stepanova (Педиатрическая фармакология)
The article illustrates current views on the balanced diet concept and the healthy diet notion. It discusses the issues related to the shortage of nutrients in children and adults, its causes, symptoms, possibility of preventive measures and correction using specialized enriched foodstuffs, vitamin and mineral supplements, dietary supplements, provides information about key food sources of vitamins and minerals, new age norms for children’s consumption of micronutrients. Key words: balanced and healthy diet, vitamins and minerals, norms for consumption of micronutrients, vitamin and mineral supplements, dietary supplements, enriched foodstuffs, children. (Pediatric Pharmacology. – 2010; 7(3):82-87)